(untitled) (Ascendens Asia Singapore – Bestlink College of the Philippines Journal of Multidisciplinary Research, 2020)
The traditional leche flan is a common dessert in the Philippines, especially for special events such as Christmas and New Year. The business location in Sto. Niño, Novaliches, Quezon City has a limited store that offers food. Hence, the researchers proposed a study of “Goday’s Combination Flan,” which is a business that offers leche flan with different kinds of toppings to make it unique and have a variety of choices for leche plan toppings. The researchers used a descriptive research method, with the administration of a survey questionnaire. The researchers surveyed 50 respondents in Sto. Niño, Novaliches, Quezon City to gather information, test the level of acceptability of the proposed business, and test the level of acceptability in terms of price, accessibility, and visibility. The researchers also applied the financial statement in the study to test the level of profitability in terms of financial viability in pursuing the proposed study. Based on the result, the proposed business got a high percentage in terms of acceptability by adding different choices in toppings to the traditional leche flan. The researchers also obtained a high percentage in terms of accessibility and visibility of the business where it will be established. Additionally, the financial statement showed that the business can earn and return the investment in the early year. Goday’s Combination Flan is a dessert made up of eggs and milk, with different kinds of toppings. Goday’s Combination Flan also ensured it has a good quality and affordable price that will surely meet or exceed the customer’s expectation. Given that the operation has a standard quality of the product and due to its uniqueness, the customers will surely be satisfied with the product. Goday’s Combination Flan has a general partnership, by which two or more people agree to share in all assets and liabilities. Goday’s Combination Flan is unique because it offers different toppings.